Genetic and phytochemical variability in Acalypha indica L - John De Britto A; GS, Rekha (Journal of Research in Biology, 2011)
In the present study, Acalypha indica L. was collected from ten locations in Tirunelveli hills and the genetic variability was investigated using RAPD-PCR fingerprint. The population which showed high percentage of polymorphism was selected. The samples from this population were chosen for further phytochemical analysis and the active principle has been quantified. The population which exhibited both high percentage of polymorphism and high amount of active principle was considered to be the superior genotype